An experimental inoculation system to study citrus-Xylella fastidiosa interactions - Lopes, S. A.; Teixeira, D. C.; Fernandes, N. G.; Ayres, A. J.; Torres, SCZ; Barbosa, J. C. (Amer Phytopathological Soc, 2005)
Difficulties in reproducing the citrus variegated chlorosis (CVC) disease symptoms in expertmental plants have delayed implementation of studies to better understand the essential aspects of this important disease. In an extensive Study, cultivars of sweet orange (Citrus sinensis) were inoculated with Xylella fastidiosa using procedures that included root immersion, and stein absorption, pricking, or infiltration of the inoculum into plants of different ages. Inoculum consisted of 5-day-old cultures or cell suspensions of CVC strain 9a5c diluted in phosphate-buffered saline. Inoculated plants and controls were grown, or transferred just after inoculation, to 5-liter pots or 72-cell foam trays. Approximately 4, 5, 9, and 12 months after inoculation, leaves were collected and processed for polymerase chain reaction analysis or X. fastidiosa isolation on BCYE agar medium. Root immersion and stem inoculation of 4- and 6-month-old plants resulted in low percentages of symptomatic (0 to 7%) and plants positive by isolation (0 to 9%). Pinpricked or injected stems of I-month-old seedlings resulted in high percentages of plants symptomatic (29 and 90% in Pera Rio, 75, 59, and 83% in Valencia, and 77% in Natal) or positive by isolation (26 and 93% in Pera Rio, 98, 96, and 83% in Valencia, and 77% in Natal), In foam trays, the seedlings grew less, the incubation period was shorter. and disease severity was higher than in pots. This system allows testing of higher numbers of plants in a reduced space with a more precise reproduction of the experimental conditions.